Dissidence politique et contreculture : le cas du carnaval de Montevideo - Dorothée Chouitem (Centre de Recherches sur les Mondes Américains, 2009)
The international bipolar situation of the 1960s left in its wake a huge social protest in Uruguay. The defense of an ideal of social justice, based on the questioning of the political system in force, was perceived by the ruling leaders – holders of the orthodox ideology – as a threat towards democracy and its values, just as the intra-social conflicts that followed had served to justify the coup of 1973. Since “the ‘carnivalesque’ time is one in which an entire society shows and frees itself”, as these festivities “set up constitutive social hierarchies in order to expose and strengthen them, or to challenge them” (Balandier, 1992), the representations of the murgas will bring about much suspicion. Thus, thinking in general terms, we will attempt to outline the changes that the murga (representative of the Uruguayan working class) will bring about and we will focus on the means the dissidents’ oblique speechresorted to, in order to live through the forced silence where the truth is no longer spoken under censorship, to make reference to the facts that the holders of the “official truth” will attempt to cover up.